(untitled) (International Journal of Engineering and Computer Science, 2016)
These In a powers system network there are many problems related to power quality. So to improve power quality of a system we use different devices such as active power filters. Active power filters are classified into two types that is Shunt Active Power Filter (APF) and Series Active Power Filter (APF) and combination of both is known as UPQC (Unified Power Quality Conditioner). Here we have done simulation of Shunt Active Power Filter, Series Active Power Filter and Unified Power Quality Conditioner. Shunt APF is used to mitigate the problems due to current harmonics which is because of non-linear load and make source current sinusoidal and distortion free. The control scheme used is hysteresis current controller using “p-q theory”. Series APF is used to mitigate problems caused due to voltage distortion and unbalance present in source voltage and make load voltage perfectly balanced and regulated. The control scheme used is Hysteresis voltage controller by using a-b-c to d-q transformations. Then Shunt APF and Series APF is combined for designing UPQC and by this current harmonics in load current and voltage unbalances in source voltage both are removed and source current becomes sinusoidal and load voltage becomes perfectly balanced.